2000
DOI: 10.1093/ajcn/72.3.780
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency bioelectrical impedance analysis in women with a normal and hypertensive pregnancy

Abstract: Our results show that multifrequency bioelectrical impedance analysis can be used to monitor variations in body water compartments in normal pregnancy and detect gestational hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 12 publications
5
52
1
4
Order By: Relevance
“…This is in line with the findings of two papers of the research group of De Lorenzo, in which they reported a moderate but significant increase of ICW during the third trimester [4,14]. They explained a slight increase of ICW at the end of gestation by the water-filling need of the breast tissue and the inferior pelvis in order to guarantee the correct course of labour, delivery and puerperium [14].…”
Section: Longitudinal Evolution Of Fluid Parameterssupporting
confidence: 89%
See 3 more Smart Citations
“…This is in line with the findings of two papers of the research group of De Lorenzo, in which they reported a moderate but significant increase of ICW during the third trimester [4,14]. They explained a slight increase of ICW at the end of gestation by the water-filling need of the breast tissue and the inferior pelvis in order to guarantee the correct course of labour, delivery and puerperium [14].…”
Section: Longitudinal Evolution Of Fluid Parameterssupporting
confidence: 89%
“…The increasing fluid parameters during an uncomplicated pregnancy found in this study, is in line with different other studies [4,[13][14][15]. The slight decrease of ECW at earlier gestation till 14 weeks as reported by Larciprete et al could not be confirmed in our study [14].…”
Section: Longitudinal Evolution Of Fluid Parameterssupporting
confidence: 79%
See 2 more Smart Citations
“…The evaluation of these components and their modifications could be of the utmost importance during pregnancy, since they can vary on an individual basis, thereby affecting GWG to a variable degree. Nowadays, there aren't studies evaluating the BIA during the different trimesters of pregnancy in obese women with the purpose of monitoring the FM and FFM increase, since the most of them namely consider the total body water [29][30][31][32]. Moreover, there are not so many studies evaluating both the adherence to a proper nutrition and the PA in obese pregnant women, namely through respectively FFQ and SWA.…”
Section: Discussionmentioning
confidence: 99%